Building Belonging through Art with Young Migrants Living in Care in South Africa - Shahrokh, Thea; Treves, Giulia (African Human Mobility Review, 2021)
As young people with migration experiences build their lives in new contexts, their connectedness to who they are, to other people, to place and to culture underpin whether and how a sense of belonging is built in their lives. Belonging as a concept matters in young lives as it is underpinned by feelings of acceptance, inclusion and selfdetermination. The realization of belonging can have important implications for young people’s wellbeing and development. This paper shares the barriers to belonging for young migrants in South Africa, and how the pain of past experiences, and the exclusions they are navigating in the present constrain their sense of agency, impacting selfworth and relationship formation. We share how a child and youth care center in Cape Town specializing in supporting young migrants and young people with experiences of trauma, innovated with a group of young women through participatory arts-based methods towards building belonging. We found that layering multiple arts methods can support young people to connect to their cultural roots and personal relationships, re-build trust, reimagine their identities as part of a collective and challenge power relations around gender, nationality and generation. We found that building belonging should be seen as a continuous learning process, that builds young people’s reflective capacities to understand self and others and to make sense of the interaction between past, present and future. In turn, belonging provides an important conceptual tool for youth-led, context-specific approaches to working with young migrants, including on youth transitions.